AB0667 Clinical and therapeutic differences between polymyositis and dermatomyositis in a colombian cohort with idiopathic inflammatory myopathy. (15th June 2017) - Fuentes, R; Vargas, F; Alzate, MA; Hernandez-Parra, D; Salazar-Uribe, JC; Ortiz-Salazar, P; Pineda, R; ,
Abstract : Background: The idiopathic inflammatory myopathies (IIM) are a group of immune-mediated systemic conditions characterized by chronic muscle inflammation, resulting in muscle weakness (1). Objectives: To characterize the disease in a Colombian cohort with idiopathic inflammatory myopathy, assessing differences in its classification, cutaneous and systemic manifestations, laboratory results, and therapeutic approach, according to the type of myopathy. Methods: A cross-sectional study was conducted in 112 patients, in whom sociodemographic, clinical and therapeutic characteristics were analyzed based on the type of myopathy. Statistical association was examined by means of Chi-square tests, Mann-Whitney test, and logistic regression analyses. Results: From the 112 patients recruited, 59 had polymyositis (PM) and 53 had dermatomyositis (DM). The patients were classified with Peter & Bohan criteria as: "definite" diagnosis 67 (60%), "probable" 35 (31%) and "possible" 9 (10%). A high proportion of males were found in this cohort. Our most notable findings are listed in Table 1, noticing for this population a high rate of polyautoimmunity associated to PM (OR 3.81 95%IC 1, 003–14, 53) and an association between ANAs antibodies positivity and DM (OR 7.03 95%IC 2, 16–22, 9). Patients with PM presented higher values of CK, LD and transaminases. Also, according to the therapeutic approach, PM was positively associated with the use of azathioprine and immunoglobulins (OR 2, 59 95%IC 1, 18–5, 69 and OR 3, 21 95%IC 1, 19–8, 19, respectively), while chloroquine and hydroxychloroquine were mainly used in DM patients. Conclusions: In this Colombian sample, a high proportion of patients were classified as definite diagnosis, high frequency of male-gender compromise, low association with cancer, and low prevalence of articular, pulmonary and cardiac involvements were found. References: Rosa J, Garrot LF, Navarta DA, Saucedo C, Scolnik M, Bedran Z, et al. Incidence and prevalence of polymyositis and dermatomyositis in a health management organization in Buenos Aires. J Clin Rheumatol. 2013;19(6):303–7. Disclosure of Interest: None declared